THE INFLUENCE OF SELF CONTROL, LIFE STYLE, AND INFLUENCER REVIEWS ON SHOPPING BEHAVIOR STUDY ON SHOPEE GEN Z CONSUMERS - Sofia Naya Febriyanti; Muhammad Yani; Lilik Indayani (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: The development of digital technology and the rapid growth of e-commerce have changed people's consumption patterns, especially among Generation Z, who are known as active users of the Shopee platform. The phenomenon of consumptive shopping behavior is increasing along with low self-control, a practical digital lifestyle, and the strong influence of influencer reviews on social media. This study aims to analyze the influence of self-control, lifestyle, and influencer reviews on the shopping behavior of Shopee consumers in Gen Z. Method: The research approach uses a quantitative method with a questionnaire distributed to 153 respondents who meet the criteria: Gen Z aged 17–28 years, active Shopee users, and have seen influencer reviews. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) through the SmartPLS 3.0 application. Results: The results showed that all independent variables, namely Self-Control, Lifestyle, and Influencer Reviews, had a positive and significant effect on Shopping Behavior. Novelty: This study contributes to understanding Gen Z consumption behavior and supports efforts to achieve SDG point 12 on sustainable consumption patterns.